The pulp healing process: from generation to regeneration. Issue 1 (27th February 2013) - Simon, Stéphane; Smith, Anthony J.; Lumley, Philip J.; Cooper, Paul R.; Berdal, Ariane
<x xml:space="preserve">Abstract</x> Dentistry has not escaped the exciting new therapeutic advances of regenerative medicine. The accumulating knowledge about dental stem cells, differentiation, and the signaling cascades of tooth development and morphogenesis has enabled the implementation of dental biomimetics. This domain offers novel approaches to oral restoration, such as whole tooth organ bioengineering and targeted regeneration of specific dental and periodontal tissues, including bone, as recently achieved in rodent models in several laboratories. These procedures have resulted in successful growth of a tooth and its periodontium with appropriate functional properties, including vascularisation, innervation and responses to biomechanical forces (1). However, the length of time required to perform tooth bioengineering has hampered the application of these procedures to the clinical setting. Nevertheless, there are several strategies that can be used to regenerate specific parts of the dental‐bone complex which have been destroyed by oral disease.